Pesan Moral pada Novel Before the Coffee Gets Cold Karya Toshikazu Kawaguchi - Ghefira Wulansari Fauzia (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
Moral problems are one of the events that occur in society in life and they are increasingly today. This is clearly something that must be considered in order to find a solution. Domestic violence is example of a moral problem, because of this, a generation of young people is born with a lack of morals. Novels, as a part of literature, can be used by authors to convey moral value. Toshikazu Kawaguchi’s Before the Coffee Gets Cold has a various moral messages for readers in its storyline. The aim of this research is to describe how moral values exist in the object of this research, especially moral values in human relationships with themselves and others. This study applied qualitative research methods. This study approach uses an objective approach and the type is known as library research. Data is collected by reading the novel, which will then be labeled and analyzed. This research also utilizes book and articles to complement the results. Based on the results of this study, moral values in human relationships with oneself including life with a positive aura, strong commietment to work, not beging too concerned with one’s own ego, the future depens on oneself, good manners and ethics, not wallowing in sadness, and the belief that everyone has the ability to overcome their problems. Moral values in human relationship with others include not jumping the queue, not interfering in other people’s business, not breaking basic rules and having the courage to right the wrongs of others.